2010
DOI: 10.1002/srin.201000063
|View full text |Cite
|
Sign up to set email alerts
|

Study of Open Eye Formation in an Argon Stirred Ladle

Abstract: Two cold models were employed to simulate the formation of open-eyes in a gas stirred ladle. In the first model, water and silicon oils were employed to simulate liquid steel and slag respectively. In the second one, liquid Ga-In-Sn alloy was used to simulate liquid steel, while 12% hydrochloric acid simulated the top slag. The experimental results indicated that the gas flow rate, height of the lower liquid and height of the top liquid had a strong impact on the open-eye size. On the other hand, the viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…In addition, many research works for slag eye formation have been carried out by other workers. 14,15) However, relatively little work has been reported on slag eye formation in ladle metallurgy with eccentric and multi-plugs gas bubbling.…”
Section: Modeling Of Gas-steel-slag Three-phase Flow In Ladle Metallumentioning
confidence: 99%
“…In addition, many research works for slag eye formation have been carried out by other workers. 14,15) However, relatively little work has been reported on slag eye formation in ladle metallurgy with eccentric and multi-plugs gas bubbling.…”
Section: Modeling Of Gas-steel-slag Three-phase Flow In Ladle Metallumentioning
confidence: 99%
“…The % error was calculated according to the following formula: It is seen from Table 1 that the percentage errors in the estimated slag 'eye' radius range from 75.27% to 99.33% which are huge. The percentage errors in the radius obtained from other researchers 7,9,11,12) which had different operating slag height to bath height ratios were even larger and hence, are not shown here. This clearly proves the fact that the correlations developed to predict the open 'eye' area in laldes can not be used for tundishes.…”
Section: Resultsmentioning
confidence: 76%
“…On comparing the present water model results with the estimates obtained from the correlations for ladles, 2,3,7,9,11,12,15) it can be concluded that the mechanism of slag 'eye' formation in a tundish is different from that in ladles, and hence, a new correlation needs to be developed for predicting the size of slag 'eye' in a tundish.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Strong turbulent flow in the ladle beneficially enhances the chemical reaction rate, homogenizes the chemical composition, removes non-metallic inclusions, and eliminates temperature stratification. In addition, enhancing turbulence at the slag/steel interface is required to achieve a desirable desulphurization result [1]. Argon gas stirring (AGS) and electromagnetic stirring (EMS) are the two dominant methods in the ladle refining process [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%